Editorial: Soil health, functions, and ecosystem services: insights into soil parameters and methods of integration - Meersmans, Jeroen; Colinet, Gilles; Negassa, Wakene (Frontiers in environmental science, 2024)
[...]improving our understanding of the response of soil properties to various management practices and environmental stressors is a prerequisite to maintain or even enhance soil functions (e.g., regulating water quality and availability, sustaining plant and animal life, filtering and buffering environmental pollutants, elemental cycling, and providing physical stability) and therefore also overall soil health and related ecosystem service performance such as climate regulation, flood and erosion protection, food and water security (Pereira et al., 2018). Since the green revolution, intensive agricultural management practices (e.g., ploughing and applying mineral fertilizers) have resulted in a considerable decrease in soil organic carbon (SOC). [...]this kind of studies are crucial in order to conduct a sustainable cropland management strategy plan with the objective to enhance soil’s total ecosystem service delivery capacity across large geographical areas.